IMPROVING COMPENSATION SYSTEM TO INCREASE EMPLOYEE SATISFACTION TOWARD SALARY IN THE STONE CAFÃ - Asiyah Hanun, Masayu
As a restaurant playing in a high competition area, The Stone Cafe needs to have employees with good performance so that they can compete with other restaurants nearby. Employee satisfaction in working at a company becomes important to ensure the employees perform well. In order to find out about employee satisfaction in The Stone Cafe, the researcher conducted a questionnaire regarding its compensation, performance appraisal, and training to the employees. Compensation, performance appraisal, and training are part of human resource management activities within a company for improving the performance. The result of this survey shows that many of the employees are already satisfied with the performance appraisal and training but 54% are not satisfied with their basic salary because the salary that they received is not compatible with the work demand and the job responsibility. Basic salary is part of compensation system and in The Stone Café itself it is the biggest component of their compensation system. The researcher then carried out an interview with the restaurant’s Assistant Manager in which he stated that there are employees who are constantly being absent from work.